The cardiotoxicity of chemotherapy - Miolo, GianMaria (Radiology and oncology (Ljubljana), 2006)
Background. Cardiotoxicity caused by chemotherapy, zuith its diverse early andlate presentations, can hamper potentially curative or palliative treatments. The drugs most often linked to cardiotoxieity include anthracyclines, trastuzumab, 5 fluorouracil and taxanes, but sorne forms of cardiotoxicity have been described, more or less sporadically, for most antitumour agents. It is likely that the widespread use of the new biological target therapies will lead to the identification of other less known toxic effects. The available data on its incidence and clinical presentation, the pathogetetic mechanisms involved, the diagnosis, prevention and management of cardiac toxieity frorn chemotherapy are briefly reviewed. Conclusions. The identification of novel rnolecular targets zuill increase the number of drugs available for the treatment of neoplastic disease. It will be important to evaluate the side effects related to treatment, particularly in organs with a limited regenerative capability such as the heart. Further studies will therefore be necessary.
Keywords: Adverse Effects; Anthracyclines; Antibodies, Monoclonal; Antineoplastic Agents; Antineoplastiki; Antraciklini; drug; Drug Effects; Fluorouracil; Heart; kardiotoksičnost; kemoterapevtiki; onkologija; Protitelesa monoklonska; Srce; stranski učinki; therapy; Toxicity; zdravila; zdravljenje